2022
DOI: 10.4149/bll_2023_008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of AGTR1, AGТ, LPL, ADRB2 gene polymorphisms on central obesity in adolescents of the Kazakh population

Abstract: BACKGROUND: Abdominal obesity, usually measured by waist circumference and waist-to-hip ratio, is more closely related to metabolic dysfunctions that are associated with cardiovascular diseases than general obesity, which is usually assessed by body mass index. The purpose of our study was to study the distribution of alleles and genotypes AGTR1, AGТ, LPL and ADRB2 among adolescents of the Kazakh population and to identify the relationship of these genes with predictors of obesity. METHODS: The study involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…PLG (plasminogen) [81] plays an indispensable role in glomerulonephritis. AFM (afamin) [82], AGTR1 [83] and IL1RL1 [84] could be an early detection biomarkers for obesity. AGTR1 [85] and UMOD (uromodulin) [86] expression is a potential target for diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PLG (plasminogen) [81] plays an indispensable role in glomerulonephritis. AFM (afamin) [82], AGTR1 [83] and IL1RL1 [84] could be an early detection biomarkers for obesity. AGTR1 [85] and UMOD (uromodulin) [86] expression is a potential target for diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…E2F1 [496], AGTR1 [74], VCAM1 [533], hsa-mir-7847-3p [804], FOXC1 [805], USF2 [796], YY1 [806], STAT3 [807] and BRCA1 [799] have been observed in sepsis patients. Studies have shown that E2F1 [669], VCAM1 [715], AGTR1 [83], hsa-mir-221 [780], YY1 [808], STAT3 [809], PDX1 [810] and BRCA1 [811] are associated with obesity. E2F1 [719] and VCAM1 [736] are altered expressed in patients with renal ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Среди многочисленных причин ожирения особое место занимают генетические факторы. К настоящему времени установлено более 100 генов, которые связаны с ожирением [5][6][7]. Очевидная роль среди них принадлежит генетическому полиморфизму ферментов, участвующих в метаболизме липидов, к числу которых относятся печеночная триацилглицероллипаза и липопротеинлипаза, а также параоксоназа-1 (PON-1) имеющие тканеспецифическую локализацию в организме [6,[8][9][10][11].…”
Section: обоснованиеunclassified
“…Tis isoform alters the blood levels of TAG, cholesterol, and HDLs; however, the data on these shifts are controversial [2,[11][12][13][14]. On the one hand, 447Ter is associated with the reduced risk of abdominal obesity [15], while on the other hand, carriers of the 447Ter genotype sufer from cardiovascular diseases more frequently [16].…”
Section: Introductionmentioning
confidence: 99%